2018
DOI: 10.1186/s12885-018-4824-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular iodine inhibits the expression of stemness markers on cancer stem-like cells of established cell lines derived from cervical cancer

Abstract: BackgroundCancer stem cells (CSC) are characterized by deregulated self-renewal, tumorigenicity, metastatic potential, aberrant stemness signaling pathways, resistance to conventional therapy, and the ability to give rise to a progeny of proliferating cells that constitute the bulk of tumors. Targeting CSC will provide novel treatments for cancer. Different investigations have focused on developing complementary approaches that involve natural compounds that decrease chemo-resistance and reduce the side effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…389 The PPARγ/NF-κB pathway promotes M2 polarization of macrophages to prevent cell death in ovarian CSCs 4.390 PPARγ activation promotes expression of its target gene PTEN to inhibit PI3K/Akt/ mTOR signaling, which stunts self-renewal, tumorigenicity, and metastasis in cervical CSCs, glioblastoma stem cells, and liver CSCs. 391,392 However, combined expression of Dnmt3a and Dnmt3b inhibits PPARγ expression by direct methylation of its promoter in squamous carcinomas. 393 PPARs are also closely related to the metabolism of CSCs.…”
Section: Major Signaling Pathways In Cscsmentioning
confidence: 99%
“…389 The PPARγ/NF-κB pathway promotes M2 polarization of macrophages to prevent cell death in ovarian CSCs 4.390 PPARγ activation promotes expression of its target gene PTEN to inhibit PI3K/Akt/ mTOR signaling, which stunts self-renewal, tumorigenicity, and metastasis in cervical CSCs, glioblastoma stem cells, and liver CSCs. 391,392 However, combined expression of Dnmt3a and Dnmt3b inhibits PPARγ expression by direct methylation of its promoter in squamous carcinomas. 393 PPARs are also closely related to the metabolism of CSCs.…”
Section: Major Signaling Pathways In Cscsmentioning
confidence: 99%
“…Similar results were obtained in trophoblast cells exposed to iodine supplementation increasing the synthesis of chorionic gonadotropin [ 84 ]. Moreover, studies related to stemness markers in breast and cervical cancer cells indicated that I 2 supplementation decreased the stem cell-like population, transforming the survival cells into non-invasive type cells incapable of generating xenografts [ 85 , 86 ]. In both conditions PPARγ receptors were increased.…”
Section: Introductionmentioning
confidence: 99%
“…The stemness supporting transcription factors, such as Sox2, Klf4, c-Myc, Oct4, and Nanog, are upregulated in various types of CSCs [22,23,[26][27][28]. Our results demonstrated that pterostilbene effectively decreased the expression levels of the major stemness transcription factors, including Sox2, Oct4, and Nanog, as well as a cell surface marker for CSCs, CD133, suggesting that the inhibitory effect of pterostilbene against cervical CSCs may be associated with the downregulation of these stemness regulators.…”
Section: Discussionmentioning
confidence: 61%
“…To explore the mechanism by which resveratrol and pterostilbene inhibit the growth and migration of cervical CSCs, their effects on the expression of transcription factors, Sox2, Oct4, and Nanog, were investigated. These transcription factors have been reported to induce stem-like properties, in HeLa cancer stem-like cells [26][27][28]. The two compounds effectively reduced the expression levels of the key stemness-related transcription factors as well as CD133, a cell surface marker for CSCs, suggesting that the inhibitory effects of resveratrol and pterostilbene against cervical CSCs may be associated with the downregulation of these stemness regulators ( Figure 8A).…”
Section: Effect Of Pterostilbene On the Expression Of Stemness Markermentioning
confidence: 89%